Das Siedlungsgefüge im südlichen Ostalgerien (Nememcha), Genese eines zentralörtlichen Systems seit Beginn der Seßhaftwerdung bis in die Postkolonialzeit - Wagner, Horst-Günter (ERDKUNDE, 1971)
The establishment and spread of regular grain cultivation has occurred in the area south of Khenchela-Tebessa (Nememcha) since about 1880 with varying temporary phases of transhumance-like economic and and settlement forms. This process was strengthened by the upheaval of the Algerian War of Liberation (1954-1962) and the regulatory interventions of State agencies since 1962 which have taken some time to become slowly tangible. Continuous growth of settlement centres is not only a consequence of rapid natural population increase, but also of a noticeable process of concentration in the entire settlement pattern. In the same connection, there was an increase in the importance of the larger settlement centres.